Characteristic alterations of quantity and quality of soil organic matter caused by forest fires in continental Mediterranean ecosystems: a solid-state 13C NMR study - Knicker, H; Almendros, G; González-Vila, F J; González-Pérez, J A; Polvillo, O (European Journal of Soil Science, 2006)
The variable effect of different types of forest fires on the quantity and quality of soil organic matter (SOM) was analysed by comparing burnt and unburnt soils from six forest ecosystems in central Spain by organic elemental analysis and solid-state 13C nuclear magnetic resonance (NMR) spectroscopy. Whole soil samples were collected 1 to 2 years after the fires and included one site affected by two fires within 2 years. The fire-affected soils showed no common pattern with respect to the amount of additional carbon (Cadd) but at all sites, the fire enhanced the aromatic-C content. The weakest fire intensity resulted in the greatest aromatic-C enrichment factor, EFI(aromatic C) indicating the greatest local accumulation of char. The respective Cadd disclosed an EFI(aromatic C) to EFI(alkyl C) ratio, Bchar, of c.1, which supports a small degree of charring. Extensive combustion and volatilization at stronger fire intensities yielded a decrease of EFI(aromatic C) and an increase in Bchar. These trends are in good agreement with fire intensity and forest fuel combustibility in the various sites and therefore these indices could be used to elucidate the quality and quantity of char input that occurs during and after forest fires. No 13C NMR evidence for substantial inputs from non-charred plant necromass was found for any of the single-burn soils. The large carboxyl-C content of Cadd is evidence of the occurrence of oxidation reactions very shortly after the fire. In comparing the single and double-burn sites, no additional char input was observed for the double-burn site, possibly because of complete combustion of young shrubs and char remains during the second fire. The large O-alkyl-C portion found in Cadd of the double-burn soil is best explained by decreased litter degradation.
Keywords: aromatic C enrichment factor; burnt and unburnt soils; Forest fires; mediterranean ecosystems (voyant); Soil organic matter

Signatures of lipid assemblages in soils under continental Mediterranean forests - Almendros, G; Sanz, J; VELASCO, F (European Journal of Soil Science, 1996)
The analysis of free lipids in 12 soils from three representative types of Mediterranean forest has been carried out in an attempt to describe diagnostic molecules reflecting differences between the ecosystems and the intensity of the soil organic matter turnover. The study centred on the analysis by gas chromatography–mass spectrometry of the soil compounds extracted with petroleum ether from soils in central Spain, developed under monospecific formations of stone pine (Pinus pined), evergreen oak (Quercus rotundifolia) and Spanish juniper (Juniperus thurifera), the lipid extracts from their leaves also being analysed as reference material. The comparison between the distribution patterns of alkanes and fatty acids in plant lipids and the corresponding soil lipids was used to assess the extent to which the former accumulate in soil or are substituted by other biogenic or diagenetic homologues. In general, the alkane patterns showed the greatest variation in soils under oak, and the differences between lipid patterns in plant and soil were greatest in the juniper forests. As indicators of the vegetation type, the soil fatty acids had little value. Up to 60 major cyclic compounds were identified, including mainly di- and sesquiterpenes, in addition to some monoterpenes and nonterpenic naphthalenes and decalins. Of these major constituents, 33 compounds were found in soil but were not present in plant extracts, and 18 compounds were identified in plants but were not in the soils. The results suggest an arrangement of the soil samples based on the composition of the signature lipid assemblages.
Keywords: GC-MS; Lipids; Lipids assemblage (voyant); mediterranean forest soils

Pesticide sorption on soils treated with evergreen oak biomass at different humification stages - Martinez-Iñigo, M J; Almendros, G (Communications in Soil Science and Plant Analysis, 1992)
Abstract The sorption of twelve pesticides (alachlor, atrazine, carbofuran, 2,4?D, 2,4?DB, methyl parathion, metoxuron, monuron, prometryne, propanil, silvex and spergon) was studied on two soil samples with a different carbonate content and treated with evergreen oak (Quercus ilex L. subsp. ballota) biomass at successive humification stages. The direct interaction between the above pesticides and lignocellulosic materials was also assayed independently. After the samples were suspended in 25 ppm pesticide solutions for 12 h, the concentrations in the supernatants were measured by derivatographic UV spectroscopy. The major fixations on the biomass of evergreen oak were found for spergon, prometryne and propanil. Except for atrazine, carbofuran, prometryne and silvex, composting the forest residue for 87 weeks significantly increased pesticide sorption. No correlations were found between the sorption values measured directly in the lignocellulosic materials and those in the soils amended with the latter, indicating the conspicuous influence of organo?mineral interactions in the soil. Calcium carbonate played an important role in pesticide sorption: the lowest pesticide retentions were observed for the samples of the soil with the highest pH, where the addition of organic matter led to the greatest enhancements. The fixation of silvex and carbofuran increased considerably when the organic matter was added to the soil with the lowest pH, whereas in the calcic soil samples the major fixation corresponded to chlorinated phenoxy acids. Possible mechanisms involved in pesticide sorption in the systems studied are discussed.
doi: 10.1080/00103629209368699
Keywords: humification; pesticide adsorption; Quercus ilex L. subsp. ballota; soil pH (PG)

An evaluation of the differences in the composition of humic acids in soils under oak and pine forest by GC-MS after mild degradation - González-Vila, F L; Almendros, G; Martin, F (Plant and soil, 1987)
Significant differences were found in the products released after eight samples of humic acids (HA's) isolated from soils under mediterranean pine and oak forests underwent mild degradation. A number of compounds, including typical degradation products of lignins, were found exclusively in the HA's from the soils under pine forests. The aliphatic constituents were more firmly retained in the HA's under oak, which presented mean values for aromatic acids lower than the humic samples from pine forests. Different types of diterpene resin acids were also found amongst the mild degradation products of HA's from the studied areas.
Keywords: Forest soils; humic acids; Lipids; mild degradation; Pinus; Quercus; resin acids